A study to evaluate the role of digital marketing on consumer buying behavior of over the counter (OTC) pharmaceutical products - NIKHIL MOHANAN; Dr. MEENAL KULKARNI; Dr. MEENAL KULKARNI (International Journal of Pharma and Bio Sciences, 2018)
Advertising in any industryis a form of marketing communication used to inspire, influence, or to an extent control an audience to take or continue to take some action. Digital marketing, on the other hand, refers to marketing methods that permit organizations to see how a campaign is performing in real-time, such as what is being viewed, how often, how long, as well as other statistics such as sales conversions.The aim of the study was to study the various digital marketing strategies used in the pharmaceutical industry and to evaluate the impact of digital marketing on consumer buying behavior of Over the Counter (OTC) Pharmaceutical products. A comprehensive questionnaire consisting of 25 questions pertaining to factors influencing the buying behavior of consumers was made and distributed through email to 200+ email ids. 101 Responses were recorded and analyzed. The results indicate thatsmartphones continue to be the device of choice for people to consume content from the Internet. The uniqueness of the Advertisement determines whether it is able to capture the attention of the audience or not. Image and video Ads were found to generate the most impact on the consumer purchase decision. Social media promotion is second only to television commercials in terms of impact of the digital advertisements. The brand name strongly influences the purchase decision while buying any OTC product. The information on OTC advertisements is not sufficient for making health decisions. It will present an idea to brands, based on where to invest in achieving their marketing objectives. Digital Marketing being the upcoming trend in the Business industry as a whole, it becomes imperative for Pharmaceutical companies to use it in their marketing campaigns. This also provides them with valuable insight into potential threats from competitors, changing industry trends, and customer preferences.